Dual role of calcium-activated potassium channels of high conductance: facilitator or limiter of NO-induced arterial relaxation? - Shvetsova, Anastasia A.; Gaynullina, Dina K.; Schmid, Johannes; Winkler, Peter; Sonsala, Isabella; Schubert, Rudolf (Frontiers in Physiology, 2025)
AimCalcium-activated potassium channels of high conductance (BKCa channels) are important contributors to vascular smooth muscle membrane potential and thus to vascular tone. BKCa channels can promote vasodilation by facilitating vessel responses to NO. BKCa channels may also serve as limiters of the anticontractile effect of NO. However, it is unclear whether BKCa channels act simultaneously as facilitators and limiters in different vascular regions. Therefore, this study tested the hypothesis that BKCa channels both facilitate and limit NO-induced vasorelaxation in multiple vessels.MethodsContractile responses of rat tail, saphenous, and left and right coronary arteries were studied using wire myography.ResultsThe NO-donor SNP reduced contractile responses induced by low concentrations of methoxamine or serotonin, respectively, in all arteries tested, both in the absence and in the presence of iberiotoxin. This anticontractile effect of SNP was larger in the presence of iberiotoxin than in its absence, i.e., functionally active BKCa channels limit the anticontractile effect of SNP. In contrast, the anticontractile effect of SNP at high concentrations of methoxamine or serotonin, respectively, in all arteries tested was smaller in the presence of iberiotoxin than in its absence, i.e., functionally active BKCa channels facilitate the anticontractile effect of SNP.ConclusionBKCa channels simultaneously limit NO-induced vasodilation at lower levels of contractility but facilitate it at higher levels of contractility in multiple vascular beds. Therefore, BKCa channels may play a dual role as facilitators and as limiters of the effect of NO, depending on the level of contractility.